DEVELOPING EFFECTIVE INTERCULTURAL COMMUNICATION SKILLS - Anorboyeva, Diyora (Журнал иностранных языков и лингвистики, 2023)
Intercultural communication skills can help improve trust and reduce miscommunication in hybrid and diverse workplaces. Effective intercultural communication has become a priority today because of the importance it has gained in the understanding of the cultural diversity of the world. Learning about other cultures and developing intercultural communication competences and skills can help facilitate the multicultural encounter and can lead to more openness and tolerance towards the significant other. Communication processes occur in specific cultural contexts, with unique normative beliefs, assumptions, and shared symbols. Culture influences what people communicate, to whom they communicate, and how they communication. This article will make you understand the basis of intercultural communication and its relevance in today’s era of globalization.